Workshop on Improving Self-Resilience through Self-Existential Discovery (Tadabbur Alam) for Researchers and Academics in A Higher Education Institution of Brunei - Ghozali, Muhamad Afifuddin; Christiana, Elisabeth; Ratnasari, Devi; Ardyanti, Asieline Wahyu Tri; Yunita, Mila; Kamal, Akmal Nasri (Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to strengthen the mental resilience and emotional well-being of researchers and academics at a higher education institution in Brunei Darussalam through a Self-Resilience Enhancement workshop based on self-existential discovery techniques using a self-existential discovery (tadabbur alam). The Community Service Team from State University of Surabaya (UNESA) organized the program in response to the high levels of stress, burnout, and workload pressure experienced by the academic community. The tadabbur alam was chosen because it can combine self-introspection, strengthening self-identity, and spiritual connection through direct observation of natural phenomena. The program resulted in an increase of self-awareness, clarity of thought, gratitude, and inner peace, and gained adaptive strategies to deal with life's stressors of participants. Participants also understood resilience not only as the ability to bounce back from setbacks, but also as an internal strength derived from self-understanding and a spiritual connection with God. This activity is an example of cross-country collaboration between UNESA and a higher education institution in Brunei Darussalam through Guidance and Counseling Study Program and Counselling and Diverse Learning Needs Unit that is relevant to be developed in a program to improve academic mental health based on Islamic values and local culture.